МОВНІ ЗАСОБИ ВИРАЖЕННЯ ПРОХАННЯ В АНГЛІЙСЬКИХ ЛИЦАРСЬКИХ РОМАНАХ XII–XV СТ. - Гродський, І.Я. (Studia Philologica, 2015)
The article considers the characteristics of the speech act of request in the Middle English romances. The analysis of language data reveals that the realization of the action proposed, the opportunity to debate, the right to retreat and to refuse may act as the response to request. Special attention is paid to the correlation between the person’s social status and language manifestation of imperative act of request.